ANTECEDENTS OF PERSONAL ENERGY MANAGEMENT EFFECT ON INNOVATIVE WORK BEHAVIOR - Dwi Murniyati; Regita Bintang Maharani; Alvina Arzety Putri (LPPM STIE YKPN Yogyakarta, 2025)
Personality is a fundamental aspect of human life that significantly influences how individuals think, behave, and interact with their environment. In student life, personality management is crucial in supporting adaptation to academic challenges, building social relationships, and making important life decisions. This study aims to examine the relationship between personality traits, personal energy management, and innovative work behaviour among students. The theoretical framework is based on the five-factor model of personality, the concept of personal management energy, and the theory of innovative work behaviour. This study employs a quantitative research approach, focusing on personality and energy management, using a questionnaire with a Likert scale. The research was distributed to respondents aged 20-49 years, resulting in a total of 119 participants. These results support the theoretical framework that combines personality traits with innovative behaviour in the context of teamwork and academic life. Future research can explore other independent variables.